FRI0522 Ultrasound-Detected Synovitis May Predict Radiographic Damage Progression in Rheumatoid Arthritis over The Next Five Years – A Prospective Cohort Study Nested in The Swiss Quality Management Program (SCQM). (15th July 2016) - Möller, B.; Zufferey, P.; Brulhart, L.; Tamborrini, G.; Nydegger, A.M.; Dan, D.; Grobety, V.; Nissen, M.J.; Staerkle, A.; Finckh, A.; Aubry-Rozier, B.; Ziswiler, H.-R.; et al.
Abstract : Background: Ultrasound and MRI are novel diagnostic imaging tools for evaluating rheumatoid arthritis (RA) disease activity in clinical research settings, but their use in daily practice is still limited. Since 2010, standardized grey scale ultrasound (GSUS) and Power Doppler ultrasound (PDUS) assessments, which are reimbursed by the Swiss health insurances, were included as an optional tool in the regular SCQM program work-up for RA patients. Objectives: To study the predictive value of GSUS and PDUS for radiographic damage progression in RA patients in an observational real life setting. Methods: For this study, all patients in the SCQM registry with at least one X-ray before and one X-ray after their first ultrasound assessment, with at least 20 of the recommended 22 joints evaluated in the SONAR score [] were included. Ultrasound-skilled rheumatologists which have attended a half-day ultrasound standardization workshop performed optional protocol-guided ultrasound examinations at their own discretion. GSUS and PDUS were scored in accordance with OMERACT standards in a semi-quantitative manner from 0 to 3 for all but the shoulder and thumb joints for a 28 joint status). Radiographic damage of hands and feet were centrally assessed by an assessor blinded to clinical and sonographic data. The present analyses were restricted to hand data. Radiographic damage progression was defined as an increase in the Ratingen Score (range 0–190) beyond the smallest detectable change of 3.3 score points. Univariate and multivariate cox-proportional hazard ratios were calculated for different arbitrary cut-off points in GSUS and PDUS. Results: In total 377 patients were included for separate analyses of PDUS or GSUS scores, Median (mean±SD) disease duration at inclusion was 6.4 (9.5±9.8) years, median Ratingen score was 9.0 and median DAS-28(ESR) at inclusion was 3.4. Thus, the majority of patients had longstanding erosive disease and at least moderate inflammatory disease activity, despite synthetic DMARDs being used in 66%, biological DMARDs in 49% and corticosteroids in 33% of patients. Using cut-off levels for definition of the "worst" 20% (GSUS=18/66, PDUS=6/66), 30% (GSUS=16/66, PDUS=4 /66) or 50% (GSUS=11/66, PDUS=2/66) in GSUS or PDUS scores, a significantly higher proportion of patients (p<0.05) with GSUS or PDUS scores higher than each of these GSUS and PDUS thresholds had radiographic damage progression in univariate analyses (power 0.7–0.9). Conclusions: Using PDUS as well as GSUS in routine care may provide valuable information to indicate increased risk for radiographic damage progression on a long-term basis in established RA. Potential effects of US examinations on later treatment decisions remained in this study unaddressed. Disclosure of Interest: B. Möller Grant/research support from: Bristol Myers Squibb AQUIRA Awards, P. Zufferey: None declared, L. Brulhart: None declared, G. Tamborrini: None declared, A. Nydegger: None declared, D. Dan: None declared, V. Grobety: None declared, M. Nissen Grant/research support from: Abbvie, Consultant for: Pfizer, MSD, A. Staerkle: None declared, A. Finckh: None declared, B. Aubry-Rozier: None declared, H.-R. Ziswiler: None declared, M. Andor: None declared, A. Atkinson: None declared, A. Scherer: None declared